СИСТЕМА КЕРУВАННЯ ВІБРАЦІЙНОЇ ПЛОЩАДКИ З ПРИВОДОМ ВІД ЛІНІЙНОГО ДВИГУНА З ПОСТІЙНИМИ МАГНІТАМИ - Бондар, Р.П. (Інститут електродинаміки НАН України, Київ, 2025)
Modern industry requires high-precision control of vibrating electromechanical systems. To optimize the operation of vibrating machines, it is important to develop control systems that balance energy efficiency and productivity across different dynamic modes. In this work, a control system for a vibrating platform driven by a permanent magnet linear motor has been developed. The control object is represented by a two-mass mechanical scheme that accounts for the elastic properties of the vibration suspension and the forces of Coulomb and viscous friction. A vibrating linear motor with a toothless stator structure is considered as the exciter of a periodic electromagnetic force. The motor’s electrical model is represented by an equivalent circuit with lumped parameters, whose values are functions of the mover’s displacement relative to the stator. Using the developed Simulink model, the resonant properties of the electromechanical system were studied, identifying the modes corresponding to the maximum values of mechanical power and efficiency. A control system for a vibrating platform driven by a permanent magnet linear motor has been developed, which tracks the phase of displacement (or acceleration) and maintains a specified current phase. Additionally, the motor current is regulated to achieve desired parameters of mechanical vibrations. The system was simulated in the Matlab/Simulink software package, and its transient processes were investigated under changes in the mass of the vibrating platform material. References 16, figures 7, tables 2.